A Systematic Literature Review on the Integration of Islamic Management Principles in Contemporary Business Practices - Jumiati, Eti; Hardiyanti, Widhian (International Journal of Law Social Sciences and Management, 2026)
This study aims to evaluate the extent to which Islamic management principles have been integrated into contemporary business practices and identify challenges and opportunities in their implementation. Using a Systematic Literature Review (SLR) approach, this study examined 68 articles published between 2020 and 2024 that were relevant to the topic. The PRISMA method was used to select and synthesize literature that met high quality criteria. The research results show that the integration of Islamic management principles, such as Islamic Business Principles, Risk Management, and Islamic Ethics, has been applied in various business sectors, with research predominantly in Indonesia. Despite the compatibility of Islamic principles with modern management theories, their application in contemporary business practices still faces significant challenges, particularly related to the dominance of conventional management systems that emphasize profitability over ethics. The implications of this research demonstrate the importance of developing a more comprehensive and practical Islamic management model, as well as the need for a framework that can help business actors integrate moral and spiritual values into their business decisions. This is expected to positively contribute to sustainability and improved business ethics in the future.